Glucocorticoid-cholinergic interactions in the dorsal striatum in memory consolidation of inhibitory avoidance training - Sanchez-Resendis, Oscar; Medina, Andrea C.; Serafín, Norma; Prado-Alcalá, Roberto A.; Roozendaal, Benno; Quirarte, Gina L. (Frontiers in Behavioral Neuroscience, 2012)
Extensive evidence indicates that glucocorticoid hormones act in a variety of brain regions to enhance the consolidation of memory of emotionally motivated training experiences. We previously reported that corticosterone, the major glucocorticoid in the rat, administered into the dorsal striatum immediately after inhibitory avoidance training dose-dependently enhances memory consolidation of this training. There is also abundant evidence that the intrinsic cholinergic system of the dorsal striatum is importantly involved in memory consolidation of inhibitory avoidance training. However, it is presently unknown whether these two neuromodulatory systems interact within the dorsal striatum in the formation of long-term memory. To address this issue, we first investigated in male Wistar rats whether the muscarinic receptor agonist oxotremorine administered into the dorsal striatum immediately after inhibitory avoidance training enhances 48-h retention of the training. Subsequently, we examined whether an attenuation of glucocorticoid signaling by either a systemic administration of the corticosterone-synthesis inhibitor metyrapone or an intra-striatal infusion of the glucocorticoid receptor antagonist RU 38486 would block the memory enhancement induced by oxotremorine. Our findings indicate that oxotremorine dose-dependently enhanced 48-h retention latencies, but that the administration of either metyrapone or RU 38486 prevented the memory-enhancing effect of oxotremorine. In the last experiment, corticosterone was infused into the dorsal striatum together with the muscarinic receptor antagonist scopolamine immediately after inhibitory avoidance training. Scopolamine blocked the enhancing effect of corticosterone on 48-h retention performance. These findings indicate that there are mutual interactions between glucocorticoids and the striatal cholinergic system in enhancing the consolidation of memory of inhibitory avoidance training.